The impact of biofuels utilisation in transport on the sustainable development in the European Union - Simionescu, Mihaela; Albu, Lucian-Liviu; Raileanu Szeles, Monica; Bilan, Yuriy (Technological and Economic Development of Economy, 2017)
The biofuels sustainability in transport depends on the energetic products demand and the limited resources. According to European legislation, the energy consumption in transport from renewable energy in the European Union should increase by 10% till 2020. Considering the environmental requests related to greenhouse gases reduction and a lower dependency on oil fuels stimulated more the biofuels production, this research empirically assessed the impact of energy consumption in transport based on biodiesel and bioethanol on sustainable development in terms of economic growth and greenhouse emissions. Using dynamic panel and panel vector-auto-regression models for European Union countries during 2010–2015, we proved that only the energy consumption in transport based on biodiesel had a positive impact on economic growth. The greenhouse emissions did not have any impact on economic growth while the energy consumption in transport based on bioethanol negatively affected the economic growth. The Granger causality tests on panel data indicated a bilateral relationship between economic growth and energy consumption in transport based on biodiesel and between economic growth and energy consumption in transport based on bioethanol. Given these empirical results, the energy policies should focus on the higher utilisation of biodiesel in transport in the EU.